2013
DOI: 10.1016/j.jcrs.2013.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Visual and optical outcomes of a diffractive multifocal toric intraocular lens

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
22
3
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 27 publications
9
22
3
7
Order By: Relevance
“…The literature contained no information on the Lentis LT lenses for any comparison to be made. With respect to the AcrySof toric multifocal lens, our results contrast with those of other studies 14 that report a lens rotation of no more than 10°; in the current study, 17.68% of patients showed a rotation of at least this amount.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The literature contained no information on the Lentis LT lenses for any comparison to be made. With respect to the AcrySof toric multifocal lens, our results contrast with those of other studies 14 that report a lens rotation of no more than 10°; in the current study, 17.68% of patients showed a rotation of at least this amount.…”
Section: Discussioncontrasting
confidence: 99%
“…24 The literature contains no reports on the Lentis LT lenses that would allow a comparison. Other studies 14 on the same multifocal lens report similar results to those of the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies (15)(16)(17) have shown the importance of considering the posterior corneal surface when determining total corneal astigma tism and planning astigmatism correction. The posterior cornea acts as a minus lens.…”
Section: The Role Of the Posterior Corneamentioning
confidence: 99%
“…Furthermore, when choosing the IOL toricity, it is desirable to leave patients with slight with-the-rule astigmatism, due to the normal tendency for astigmatism to drift against-the-rule with advancing age. Thus, leaving this slight with-the-rule astigmatism prolongs the period of time in which the patient's corneal astigmatism is compensated by the toric IOL (15,23,33,48) .…”
Section: Calculating Toric Iol Powermentioning
confidence: 99%
See 1 more Smart Citation